# 10th Class Mathematics Introduction to Trigonometry Introduction To Trigonometry

Introduction To Trigonometry

Category : 10th Class

Introduction to Trigonometry

As we know, the trigonometry is the branch of Mathematics in which we study about the relationship between angles and its sides. In this chapter, we will discuss about trigonometric ratios which are defined in a right-angled triangle.

Trigonometrical Ratios

In the given triangle ABC, $\angle B=90{}^\circ$and let angle C is$\theta$.

Then the trigonometrical ratios are defined as follows:

• $\sin \theta =\frac{Perpendicular}{Hypotenuse}=\frac{AB}{AC}$
• $\cos \theta =\frac{Base}{Hypotenuse}=\frac{BC}{AC}$
• $\tan \theta =\frac{Perpendicular}{Base}=\frac{AB}{BC}$
• $\cot \theta =\frac{Base}{Perpendicular}=\frac{BC}{AB}$
• $\sec \theta =\frac{Hypotenuse}{Base}=\frac{AC}{BC}$
• $cosec\theta =\frac{Hypotenuse}{\operatorname{Perpendicular}}=\frac{AC}{AB}$

Relationship between T-ratios

$\sin \theta =\frac{1}{\operatorname{cosec}\theta },\,\,\cos \theta =\frac{1}{\sec \theta }\,\,and\,\,\cot \theta =\frac{1}{\tan \theta }$

From the above, we conclude that sine of an angle is reciprocal to the cosec of that angle and so on.

Tringonometric Ratios of Complementary Angles

• $\sin \,\,(90{}^\circ -\theta )=\cos \theta$$\frac{1}{2}$
• $\cos \,\,(90{}^\circ -\theta \,\,)=\,\,\sin \theta$
• $\tan \,\,(90{}^\circ -\theta \,\,)=\,\,\cot \theta$
• $\cot \,\,(90{}^\circ -\theta \,\,)=\,\,\tan \theta$
• $\sec \,\,(90{}^\circ -\theta \,\,)=\,\,\cos ec\theta$
• $\cos ec\,\,(90{}^\circ -\theta \,\,)=\,\,\sec \theta$

Trigonometric Identities

The trigonometric ratios of an angle $\theta$ is said to be a trigonometric identity if it is satisfied for ail values of 9 .In this chapter we will learn about following identities.

• ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1$
• ${{\sec }^{2}}\theta =1+{{\tan }^{2}}\theta$
• $cose{{c}^{2}}\theta =1+{{\cot }^{2}}\theta$

T-ratios of Some Standard Angles

 Angle $\to$ Ratios$\downarrow$ $0{}^\circ$ $30{}^\circ$ $45{}^\circ$ $60{}^\circ$ $90{}^\circ$ $\sin \theta$ 0 $\frac{1}{2}$ $\frac{1}{\sqrt{2}}$ $\frac{\sqrt{3}}{2}$ 1 $\cos \theta$ 1 $\frac{\sqrt{3}}{2}$ $\frac{1}{\sqrt{2}}$ $\frac{1}{2}$ 0 $\tan \theta$ 0 $\frac{1}{\sqrt{3}}$ 1 $\sqrt{3}$ Not Defined $\cot \theta$ Not Defined $\sqrt{3}$ 1 $\frac{1}{\sqrt{3}}$ 0 $\sec \theta$ 1 $\frac{2}{\sqrt{3}}$ $\sqrt{2}$ 2 Not Defined $\cos \text{ec}\theta$ Not Defined 2 $\sqrt{2}$ $\frac{2}{\sqrt{3}}$ 1

Example:

$\cos ec\theta -\cot \theta =a$, then the value of $\cot \theta$is:

(a) $\frac{a-1}{2a}$                  (b) $\frac{1-{{a}^{2}}}{2a}$

(c) ${{a}^{2}}-1$                    (d) $\frac{{{a}^{2}}-1}{{{a}^{2}}+1}$

(e) None of these

Explanation: Here it is given that          … (i)

We know that, $\cos e{{c}^{2}}\theta -{{\cot }^{2}}\theta =1$

$\Rightarrow \,\,\cos ec\theta +\cot \theta =\frac{1}{\cos ec\theta -\cot \theta }$

$\Rightarrow (\cos ec\theta +\cot \theta )=\frac{1}{a}$                 … (ii)

$\Rightarrow \cot \theta =\frac{1-{{a}^{2}}}{2a}$

Example:

The value of $\frac{{{\sin }^{2}}60{}^\circ +{{\cos }^{2}}30{}^\circ }{{{\sin }^{2}}45{}^\circ }$ is:

(a) $\frac{1}{2}$                                   (b) $\frac{1}{4}$

(c) 3                              (d) 1

(e) None of these

Explanation:  $\frac{{{\left( \frac{\sqrt{3}}{2} \right)}^{2}}+{{\left( \frac{\sqrt{3}}{2} \right)}^{2}}}{\left( \frac{1}{\sqrt{2}} \right)}=\frac{\frac{6}{4}}{\frac{1}{2}}=\frac{12}{4}=3$

Example:

The value of $2({{\cot }^{2}}45{}^\circ +{{\sec }^{2}}30)$

$-6(ta{{n}^{2}}45{}^\circ -co{{\sec }^{2}}60{}^\circ )$

(a) $\frac{4}{7}$                                   (b) $\frac{20}{3}$

(c) $\frac{3}{20}$                                 (d) $\frac{1}{3}$

(e) None of these

Explanation: Given trigonometric expression is:

$2(\cos {{t}^{2}}45{}^\circ +{{\sec }^{2}}30{}^\circ )$$-6(ta{{n}^{2}}45{}^\circ -co{{\sec }^{2}}60{}^\circ )$

$=2\left[ 1+{{\left( \frac{2}{\sqrt{3}} \right)}^{2}} \right]$ $-\,\,6\left[ 1-{{\left( \frac{2}{\sqrt{3}} \right)}^{2}} \right]$

$=2\left[ 1+\frac{4}{3} \right]-\,\,6\,\,\left[ 1-\frac{4}{3} \right]=\frac{20}{3}$

##### Notes - Introduction To Trigonometry

You need to login to perform this action.
You will be redirected in 3 sec